Challenges and Strategies in Teaching English to Heterogeneous Classes: A Case Study - Sri Gustiani (Edukasi, 2019)
Heterogeneous classes, also known as mixed-ability classes, in English competency have been threatening to teachers of English at State Polytechnic of Sriwijaya. The effects of teaching English to the heterogeneous classes at Polytechnic of Sriwijaya have been a calling for this study to provide suggesting solutions for the English teachers in this institution. Using purposive sampling, there were eight teachers of English who participated in this study. They were grouped into teachers of English who taught in: (1) engineering departments; and (2) commerce departments. The collected data via individual semi-structured interviews and a focus group interview were analyzed using thematic analysis. The results revealed that there was frequency in the case of challenges like students’ different learning styles and interest, teaching and learning materials as well as its methodology in teaching the heterogeneous classes which, in turned, needed appropriate solutions. The most effective solutions in handling the heterogeneous classes in English learning were applying differentiated instructions, and appropriate classroom management. However, these solutions did not relate to the departments where the teachers of English placed. In fact, student-centered approach is the best strategy in this situation.